Contributions of SpoT Hydrolase, SpoT Synthetase, and RelA Synthetase to Carbon Source Diauxic Growth Transitions in Escherichia coli - Fernández-Coll, Llorenç; Cashel, Michael (Frontiers in Microbiology, 2018)
During the diauxic shift, E. coli exhausts glucose and adjusts its expression pattern to grow on a secondary carbon source. Transcriptional profiling studies of glucose-lactose diauxic transitions reveal a key role for ppGpp. The amount of ppGpp depends on RelA synthetase and the balance between a strong SpoT hydrolase and its weak synthetase. In this study, mutants are used to search for synthetase or hydrolase specific regulation. Diauxic shifts experiments were performed with strains containing SpoT hydrolase and either RelA or SpoT synthetase as the sole source of ppGpp. Here, the length of the diauxic lag times is determined by the presence of ppGpp, showing contributions of both ppGpp synthetases (RelA and SpoT) as well as its hydrolase (SpoT). A balanced ppGpp response is key for a proper adaptation during diauxic shift. The effects of one or the other ppGpp synthetase on diauxic shifts are abolished by addition of amino acids or succinate, although by different mechanisms. While amino acids control the RelA response, succinate blocks the uptake of the excreted acetate via SatP. Acetate is converted to Acetyl-CoA through the ackA-pta pathway, producing Ac-P as intermediate. Evidence of control of the ackA-pta operon as well as a correlation between ppGpp and Ac-P is shown. Finally, acetylation of proteins is shown to occur during a diauxic glucose-lactose shift.